Examining the responsiveness of the National Health Insurance Fund to people living with hypertension and diabetes in Kenya: a qualitative study - Oyando, R; Were, V; Willis, R; Koros, H; Kamano, JH; Naanyu, V; Etyang, A; Mugo, R; Murphy, A; Nolte, E; Perel, P; Barasa, E (BMJ Publishing Group, 2023)
Objectives To assess the responsiveness of the National Health Insurance Fund (NHIF) Supa Cover benefit package to the needs of individuals with diabetes and hypertension in Kenya.